National Defense as fiscal policy during the Mauricio Macri administration (2015-2019) - Eissa, Sergio Gabriel (2020)
This article argues that the Defense policies implemented by the Mauricio Macri administration (2015-2019) were subordinated to the priorities defined by the neo-liberal fiscal adjustment programs executed during its tenure. In order to show this, the discourse of major policy makers is surveyed, the main policy documents published during the period are examined, and finally, the resources actually allocated to carry out Defense policies are tallied. The materials reviewed disclose a three-way dispute inside the administration. The conflict opposed those who i) Wanted to involve the military in the war against drugs, following US preferences, ii) Those who saw the military as a bloated and expensive organization that weighed excessively on the Government´s budget, and iii) and those who advocated redeploying the military as an anti-crime outfit, as a means to safeguard its budget, preserve a socially legitimate role for it and indirectly fund its main traditional national defense role.  The article establishes that, although the security-oriented discourse was apparently predominant, in the end, a fiscal adjustment rationale prevailed over all the other proposals. In consequence, economic priorities resulted that, at the end of the Macri administration, the capabilities of the Argentinean armed forces were further degraded from their 2015 level.